2015
DOI: 10.1002/app.42135
|View full text |Cite
|
Sign up to set email alerts
|

The self‐healing mechanism of an industrial acrylic elastomer

Abstract: The self-healing materials attract a lot of attention as self-healing ability considerably improves reliability of service and extends the life time of materials. However, the present self-healing materials lack the mechanical strength and thus cannot be used in practical applications. The industrial elastomer (VHB 4910) is a strong polymer, which has been used as dielectric actuator. Surprisingly, we observed that VHB 4910 has autonomic self-healing ability. As this is an acrylic polymer, we analyzed the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…From the DSC results, we deduced that hydrogen bonding between PEG and carboxyl groups hinders the crystallization of PEG chains, so the mobility of the PEG chains increased. Flory's theory indicates that the mobility of molecular chains increases with the temperature . We noticed that the self‐healing property of this polymer should be assisted with heating, and the healing efficiency increased as the temperature increased [as shown in Figure (c)].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…From the DSC results, we deduced that hydrogen bonding between PEG and carboxyl groups hinders the crystallization of PEG chains, so the mobility of the PEG chains increased. Flory's theory indicates that the mobility of molecular chains increases with the temperature . We noticed that the self‐healing property of this polymer should be assisted with heating, and the healing efficiency increased as the temperature increased [as shown in Figure (c)].…”
Section: Resultsmentioning
confidence: 96%
“…After cutting into two pieces, the cut faces of the sample will approach a new equilibrium state, which may cause the polymer to lose the ability to self‐heal. Furthermore, we tested the influence of waiting time on the self‐healing ability . We found that the polymer PEG6000‐20%‐MDI‐DMPA still demonstrated an excellent self‐healing ability even when the healing was conducted 72 h after cutting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic self-healing polymers often rely on reversible chemical reactions allowing the material to transport matter into the damaged site enabling healing by subsequentc rosslinking the transported matter to the undamaged material. In this context,v ibrationals pectroscopy like, for example, IR-absorption [17,18] or linear Raman [19,20] spectroscopy are very powerful tools to characterize self-healing materials on am olecular level. Molecular interactions and reactions utilized for the crosslinking process in intrinsic self-healing polymers [2,6] include but are not limited to hydrogen bonds, [7] metal-ligand interactions, [8] halogen bonds, [9] Diels-Alder reactions [10,11] as well as thiol-ener eactions.…”
Section: Introductionmentioning
confidence: 99%